1994
DOI: 10.1080/01904169409364709
|View full text |Cite
|
Sign up to set email alerts
|

Effects of foliar urea‐ and triazone‐nitrogen, with and without boron, on cotton

Abstract: Optimal lint yield in recently released high-yielding upland cotton (Gossypium hirsutum L.) cultivars requires careful nutrient management. It is not known whether these cultivars are capable of responding to foliar nitrogen (N) and boron (B) fertilizer when conventional soil fertility practices are used. The objectives of this study were (i) to determine the responses of a high-yielding cotton cultivar to foliar N and B fertilizer and (ii) to compare two N sources when applied to foliage of cotton. A two-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
(22 reference statements)
1
2
1
Order By: Relevance
“…The Solubor preparation contained some Na, but the increase in leaf blade Na from the foliar B application was small, and there were apparently no adverse effects from the Na. In a previous study, leaf blade Na concentrations were higher than those reported here and were negatively correlated to lint yield (Heitholt, 1994).…”
contrasting
confidence: 79%
“…The Solubor preparation contained some Na, but the increase in leaf blade Na from the foliar B application was small, and there were apparently no adverse effects from the Na. In a previous study, leaf blade Na concentrations were higher than those reported here and were negatively correlated to lint yield (Heitholt, 1994).…”
contrasting
confidence: 79%
“…Failure of the urea additives to enhance B uptake is consistent with Heitholt (1994), who reported that addition of urea to boric acid sprays on cotton failed to increase leaf B. Nitrogen applied in urea sprays is absorbed by apple leaves (Fallahi et al, 2002b;Toselli et al, 2002); hence, some of the spray-applied N likely was absorbed by the fl ower clusters and some retained as spray residue on the unwashed fl ower cluster surfaces. The total Kjeldahl analytical procedure measures N present in urea as well as in most other N compounds, so it should have detected N contributed by the N-Boron and Coron.…”
Section: Discussionsupporting
confidence: 77%
“…In many studies, normal N fertilization practices were used, then foliar N treatments were imposed on plants which had received adequate N nutrition. In the presence of adequate soil applied N, no significant response to foliar N was reported by Bednarz et al (1992), Heitholt (1994), Hodgson and Macleod (1988), Jenkins et al (1982), Solares-Pareja andMalm (1988), or Smith et al (1987). In other cases, the response to foliar applied N was very small when compared to the variability between plots, therefore it was difficult to confirm a statistically significant response.…”
Section: Introductionmentioning
confidence: 80%
“…Boquet et al (1993;1994) showed that excessive N application decreased boll production at lower fruiting sites while increasing production of smaller, later maturing bolls on the upper fruiting sites of the plant. Other problems associated with excess N availability are excessive vegetative growth, increased boll rot due to shading of lower bolls, increased insect pressure and more difficult defoliation.…”
Section: Introductionmentioning
confidence: 98%